Cutting balloon for the treatment of resistant pulmonic valve stenosis. (October 2011) - Gavri, Sagui; Perles, Zeev; Golender, Julius; Nir, Amiram; Ellaham, Nael; Rein, Azaria
Background: Congenital pulmonic valve stenosis comprises 7.5–9% of congenital heart defects. The treatment of choice is percutaneous balloon valvuloplasty; however, a small percentage of patients have thick and flexible valve leaflets (dysplastic valves) that require surgical valvotomy. We aim to report our experience using a cutting balloon and repeated balloon dilation as a last attempt before surgical referral.Methods: Between June 2005 and November 2010, we treated 50 patients with isolated pulmonic valve stenosis. Five patients (10%) had thick and dysplastic pulmonic valve leaflets that were resistant to repeated balloon dilation attempts. We attempted to create a tear in the dysplastic pulmonic valve by performing pulmonic valvotomy using a cutting balloon (Boston Scientific, Natick, MA, USA), which was advanced through a long sheath, followed by repeated standard balloon dilation.Results: There was no change in the peak systolic gradient at catheterization after conventional pulmonic valve balloon dilation. However, a reduction of 37% was observed, during catheterization, after cutting balloon dilation and additional standard balloon dilation (p = 0.09). Echocardiographic follow-up showed a 23% decrease of the maximum instantaneous gradient early after cutting balloon dilation of the pulmonic valve (from 75 ± 15 to 58 ± 4 mmHg, p = 0.05). There was no restenosis of the valve (50 ± 13 mmHg) at long-term 5.5 years ± 9 months follow-up (range 4.5–6 years) and no complications.Conclusion: The use of cutting balloon is a possible option for the treatment of resistant congenital pulmonic valve stenosis before referral for surgical valvotomy. A larger controlled trial is needed to assess the effectiveness and safety of the procedure and validate our experience in this small series.